Genotoxicity evaluation of the insecticide endosulfan in the wetland macrophyte Bidens laevis L. - Pérez, Débora Jesabel (2008)
The frequency of micronuclei (MN) and chromosome aberrations in anaphase telophase (CAAT) was determined in root tips of the wetland macrophyte Bidens laevis exposed to environmentally relevant concentrations of endosulfan (0.01, 0.02, 0.5 and 5 mg/L) for 48 h. MN frequency varied from 0 in negative controls and plants exposed to 0.01mg/L endosulfan to 0 to 3 in plants exposed to 5 mg/L. Moreover, a significant concentration-dependent increase of CAAT was observed. The higher proportion of laggards and vagrand chromosomes observed at 5 mg/L would indicate that endosulfan interacts with the spindle interrupting normal chromosome migration. Endosulfan resulted genotoxic to B. laevis, a species of potential value for bioassays and in situ monitoring of environmental contamination by pesticides.